Introduction of a new Rotavirus vaccine: Initial results of uptake and impact on laboratory confirmed cases in Anglia and Essex, United Kingdom, July 2015. Issue 4 (2nd April 2016) - Inns, Thomas; Trindall, Amy; Dunling-Hall, Sara; Shankar, Ananda Giri
Abstract: Rotavirus gastroenteritis accounts for an estimated 130, 000 GP consultations and 13, 000 hospitalisations for children under 5 y old each year in England and Wales. In July 2013, an oral live attenuated rotavirus vaccine (Rotarix®) was introduced into the UK infant immunisation program as a 2 dose schedule at 2 and 3 months of age. We collected vaccination uptake from October 2013 to March 2015 and laboratory confirmed cases data on children under the age of 5 y from 1 January 2004 to 31 May 2015. The vaccine uptake rates and laboratory confirmed cases were compared to provide evidence of the impact of this vaccination program. Vaccine uptake rates were available from sentinel data with between 91–98% of GP practices in Anglia and Essex providing data every month. These data showed from February 2014 to March 2015 between 90–92% of infants received the recommended 2 doses of Rotarix® each month. The numbers of rotavirus cases reported by laboratories decreased on average by 82% in the post vaccination seasons. The mean number of cases reported in weeks 1–22 for 2004–2013 in Anglia and Essex was 1, 318. For the same period in 2014, 256 cases were reported and initial data for 2015 report 226 cases. In the first 5 months 2014 the greatest reduction in cases (89%) was seen in those under 1 yr (who would have been directly affected by vaccination) with case numbers falling to 59 from a mean 537 cases in the equivalent period for 2004–2013. Initially data suggests a 92% reduction in 2015 compared to the same pre-vaccination periods. For those aged 1 to <5 y who would not have been vaccinated, a reduction of 75% was also evident in 2014 and 77% in 2015, suggesting indirect protection in this group. In conclusion, initial results following the introduction of the Rotavirus vaccine clearly indicates a very good uptake of the vaccine and a significant reduction in the numbers of laboratory confirmed cases.